PERAN IMAN KRISTEN DALAM MEMBENTUK KARAKTER DAN ETIKA GENERASI MUDA DI ERA DIGITAL - Ferdi Arison Ga Djami; Harun Y. Natonis (CV. ADIBA AISHA AMIRA, 2025)
The advancement of digital technology has significantly influenced the way young people think, behave, and interact. The rapid flow of information, exposure to global cultures, and the influence of social media often challenge traditional moral and ethical values. In this context, Christian faith plays a vital role as a strong spiritual and moral foundation for the younger generation. Christian teachings emphasize love, honesty, integrity, and responsibility as core principles for character development. Through Christian religious education in the family, church, and schools, young people can be guided to live according to biblical values and to discern between right and wrong. The inculcation of these values must be contextualized to remain relevant in addressing the challenges of the digital era, such as exposure to harmful content, ethical relativism, and identity confusion. This article aims to explore how Christian faith can serve as a transformative force in shaping the ethical and moral character of the younger generation, and to offer applicable strategies for parents, churches, and educational institutions to foster spiritually grounded and ethically responsible youth.